2015
DOI: 10.7150/jca.11709
|View full text |Cite
|
Sign up to set email alerts
|

Genes Regulating Epithelial Polarity Are Critical Suppressors of Esophageal Oncogenesis

Abstract: Esophageal cancer is an aggressive disease featured by early lymphatic and hematogenous dissemination, and is the sixth leading cause of cancer-related deaths worldwide. The proper formation of apicobasal polarity is essential for normal epithelium physiology and tissue homeostasis, while loss of polarity is a hallmark of cancer development including esophageal oncogenesis. In this review, we summarized the stages of esophageal cancer development associated with the loss or deregulation of epithelial cell apic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…ESCC is the most prevalent histopathologic subtype of EC in central regions of China, especially in Henan province [ 14 ]. Despite of the recent rapid advances in the diagnosis and treatment, survival of ESCC patients with recurrence or metastasis remains unfavorable [ 15 , 16 ]. The improvement of ESCC survival rate requires a clear understanding of pivotal molecular mechanisms from the initiation and progression of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…ESCC is the most prevalent histopathologic subtype of EC in central regions of China, especially in Henan province [ 14 ]. Despite of the recent rapid advances in the diagnosis and treatment, survival of ESCC patients with recurrence or metastasis remains unfavorable [ 15 , 16 ]. The improvement of ESCC survival rate requires a clear understanding of pivotal molecular mechanisms from the initiation and progression of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…PAR complex, an evolutionarily conserved protein complex among multicellular organisms from worms to humans, is important for maintenance of epithelial polarity and its dislocation or dissociation is involved in epithelial tumorigenesis and metastasis [11, 12]. As reported, loss of Par3, a key component of the PAR complex, is found to be tightly correlated with lymph node metastasis in esophageal squamous cell carcinoma [13]. Our previous work also demonstrated that dissociation of PAR complex by Shp2 contributes to metastasis in prostate cancers via induction of epithelial-to-mesenchymal transition (EMT) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal localization of claudin-7 promotes cell transformation and regulates E-cadherin expression during tumor progression. 48 , 49 Loss of claudin-7 expression in oral squamous cell carcinoma was associated with high pathological grade, TNM staging, vascular invasion, and regional lymph node involvement. 50 Claudin-7 expression was also significantly associated with histological grade and distant metastasis in breast cancer 51 , 52 and endometrial cancer, 53 and it had prognostic significance.…”
Section: Claudin-7 and Cancer: Causal Correlationmentioning
confidence: 99%